A Comparative Study Between Conventional Concrete and Concrete Made from Plastic Waste by Using SolidWorks Software - Ali, Roslinda; Sze, Sharon Ting Shu; Marsi, Noraini (Journal of Advanced Industrial Technology and Application, 2023)
Production of conventional concrete leads to several negative impacts on the environment while the plastic waste concrete can effectively overcome the environmental issues and having better performance than conventional concrete. Therefore, this research presents the works in producing new concrete by replacing the fine aggregates in concrete by using a mixture of soft and hard plastic waste with different ratios density. In addition, this research also aims to evaluate the mechanical and physical properties of different ratios of fine aggregate plastic waste in producing a concrete. At the end of this research, a comparison is made between the optimum composition of plastic waste concrete and conventional concrete. This study is conducted by using SolidWorks software version 2021. The tests conducted include compressive strength test, drop test, and failure analysis. The results from the compressive strength test revealed that a force at 100kN with 20% plastic waste (Sample B) showed the highest stress (18.91 MPa). Meanwhile, from the drop height of 2.0m, the impact strength of Sample B showed the highest result with a value of 7.830 x106 N/m2. However, failure analysis results revealed that Sample B has more cracking than Sample A. From the study carried out, it can be summarised that an optimum replacement of 20% plastic waste as fine aggregates in a concrete gives the best performance is the most suitable option to be used as a replacement concrete in lightweight construction.